Strengthening media literacy through intensive reading–listening skills in higher education: Information processing framework - Lestari, Nurul Dwi; Anwariyah, Anwariyah; Ekici, Gail (Universitas Ahmad Dahlan, 2026)
Intensive reading and listening skills are things that need to be optimized for students of the Indonesian Language Education Study Program at UIN Kediri. This is because the profile of graduates of this study program, one of which is to become novice educators in the field of Indonesian. This study aims to describe (1) the dominance of micro skills in understanding academic discourse, (2) the limitations of macro-level meaning in intensive reading and listening, and (3) the reconstruction of micro-macro relationships in language learning theory. The method in this study uses a mixed research method that combines qualitative and quantitative methods. This study uses a Concurrent Design model. The results of the study show that of the six indicators of intensive reading skills, there is one indicator that needs to be improved, namely the ability to find the main idea. Meanwhile, the other five indicators have met the effectiveness aspect. As for the four indicators of intensive listening skills, there are two indicators that need to be improved, namely inferential listening and reorganization. Learning innovations as an implication of these findings, among others, can be carried out through the use of gradual scaffolding, development of question banks, combining bottom-up and top-down strategies, paraphrasing activities, identifying keywords, utilizing HOTS questions, and other innovative exercises.